Between Reality and Virtuality: A Study of Muslim Perceptions of Metaverse Hajj as a Religious Practice - Hasse Jubba; Henky Fernando; Yuniar Galuh Larasati; Muhammad Rifai Darus (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study explores Muslim perceptions and evaluations of virtual Hajj within the metaverse, focusing on its acceptance as a religious practice. Methodology: Utilising a qualitative descriptive approach, data were sourced from online news articles identified using the search term